The Effect of Compensation, Work Environment, and Training on The Performance of Production Employees PT Mestindo Gresik - Muhammad Za'qi; Roziana Ainul Hidayati; Heru Baskoro (Universitas Muhammadiyah Gresik, 2022)
The background in this study is that there are many problems that affect employee performance and this is a challenge for companies in managing human resources because the success of a company depends on quality human resources. target. This study aims to test the Effect of Compensation, Work Environment, and Training on the Performance of Production Employees of PT Mestindo Gresik. This research uses quantitative methods. The population in this study was the production employees of PT Mestindo Gresik, amounting to 78 people, while the sampling used the Non Probability Sampling technique using a saturated sample. The reason is because the sampling of the population is less than 100. The sample studied by the researcher is 78 production employees. The analysis technique uses instrument testing, classical assumption test, and hypothesis testing. For the test tool, the Statistical Package for the Social Sciences (SPSS) is used. The results of this study indicate that compensation has a positive and significant effect on employee performance, the work environment has a positive and significant effect on employee performance, and training has a positive and significant effect on employee performance.